Effect of beta‐blockade on quantitative microvolt T‐wave alternans in 24‐hour continuous 12‐lead ECG recordings in patients with long QT syndrome. Issue 4 (6th February 2019) - Takasugi, Nobuhiro; Takasugi, Mieko; Goto, Hiroko; Kuwahara, Takashi; Kawasaki, Masanori; Verrier, Richard L.
Abstract: Background: The aim of study was to investigate effects of beta‐blockade on microvolt T‐wave alternans (TWA), a precursor of lethal arrhythmia, in patients with long QT syndrome (LQTS). Methods: Eleven consecutive LQTS patients, types 1 ( n = 6), 3 ( n = 2), and "non‐1, non‐2, non‐3" ( n = 3) were enrolled. All patients underwent 24‐hr continuous 12‐lead ECG monitoring before and after initiation of beta‐blockade therapy. TWA was measured using the modified moving average method. Results: Seven (63.6%) of the 11 patients studied were symptomatic, with history of cardiac arrest or documented Torsade de Pointes (TdP) in 4 and syncope in three patients. After a median follow‐up of 34 months, beta‐blockade reduced the number of symptomatic patients to 1 with TdP ( p < 0.02), in whom TdP frequency decreased from 25 events/60 months (0.42 event/month) to seven events/69 months (0.1 event/month). In association with this reduction in symptoms, peak TWA decreased by 47% in the cohort after a median of eight months of beta‐blockade therapy [from 95 (74–130) to 50 (39.5–64.5) µV, p = 0.01]. All patients exhibited TWA ≥42 µV before beta‐blockade therapy, which eliminated these episodes in four patients. Daily frequency of TWA ≥42 µV episodes decreased by 87% [from 15 (6–26) to 2 (0–5) episodes/day, p = 0.009]. Conclusions: This study is limited by the small sample size and is mainly hypothesis generating. TWA monitoring deserves further evaluation as a risk marker and a guide to therapy in LQTS patients in future large‐scale studies.